1999
DOI: 10.1111/j.1540-8167.1999.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroporation on the Transmembrane Potential Distribution in a Two‐Dimensional Bidomain Model of Cardiac Tissue

Abstract: These results indicate that electroporation of the cardiac membrane plays an important role in the distribution of Vm induced by defibrillation strength shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…There are exceptions. For example, Aguel et al, 31 Skouibine et al, 32 and Ashihara et al 33 included electroporation in their simulations, and found significant quantitative effects. Similarly, Bray and I 34 found that electroporation did indeed keep V m from becoming extremely large near an electrode.…”
Section: Invalid Assumptions In the Simulationsmentioning
confidence: 99%
“…There are exceptions. For example, Aguel et al, 31 Skouibine et al, 32 and Ashihara et al 33 included electroporation in their simulations, and found significant quantitative effects. Similarly, Bray and I 34 found that electroporation did indeed keep V m from becoming extremely large near an electrode.…”
Section: Invalid Assumptions In the Simulationsmentioning
confidence: 99%
“…These effects are important to defibrillation success and to the susceptibility for further arrhythmias (34), and they are critical for the accuracy of computational models of defibrillation (1,3,11,27). However, longer-term effects have not been studied in intact hearts, but should be considered, since electroporation can be irreversible.…”
mentioning
confidence: 99%
“…In the absence of a better strategy, strong electrical shocks have remained the only reliable treatment for cardiac fibrillation. Over the years, biophysically-detailed multi-scale models of defibrillation [3,6,105,107] have made major contributions to understanding how defibrillation shocks used in clinical practice interact with cardiac tissue [7,9,11,29,50,78,103,104,115,118]; these models have been validated by comparing to the results of optimal mapping experiments [20,24,25]. Computer modeling of whole-heart defibrillation has been instrumental in the development of the virtual electrode polarization (VEP) theory for defibrillation.…”
Section: Simulation Of Cardiac Arrhythmia Terminationmentioning
confidence: 99%